Luminous atmospheres - Mikkel Bille (Ambiances)
This article discusses the implementation of energy saving light bulbs in Denmark. It argues that such new climate technologies are part of an increasingly politicization of ‘atmosphere’ by linking the environmental imperative to decelerate impact on the earth’s atmosphere with the everyday experiences of space through changes in visual expression. The article shows how enmity against new lighting technologies in Denmark is based on cultural notions and preferences towards shaping ‘cosy spaces’, and thereby offers insight into the social life of light. By focusing on the poor lighting quality of the energy saving light bulbs, the article shows how atmospheres are shaped by, and sometimes in contrast to, political ambitions.